Recent evidence for a strengthening CO2 sink in the Southern Ocean from carbonate system measurements in the Drake Passage (2002–2015). Issue 18 (18th September 2015) - Munro, David R.; Lovenduski, Nicole S.; Takahashi, Taro; Stephens, Britton B.; Newberger, Timothy; Sweeney, Colm
Abstract We present a 13 year (2002–2015) semimonthly time series of the partial pressure of CO2 in surface water (pCO2surf) and other carbonate system parameters from the Drake Passage. This record shows a clear increase in the magnitude of the sea‐air pCO2 gradient, indicating strengthening of the CO2 sink in agreement with recent large‐scale analyses of the world oceans. The rate of increase in pCO2surf north of the Antarctic Polar Front (APF) is similar to the atmospheric pCO2 (pCO2atm) trend, whereas the pCO2surf increase south of the APF is slower than the pCO2atm trend. The high‐frequency surface observations indicate that an absence of a winter increase in total CO2 (TCO2) and cooling summer sea surface temperatures are largely responsible for increasing CO2 uptake south of the APF. Muted winter trends in surface TCO2 also provide temporary stability to the carbonate system that is already close to undersaturation with respect to aragonite.